Aid and development by design: local solutions to local problems. Issue 2 (17th February 2019) - Flint, Adrian; Meyer zu Natrup, Christian
ABSTRACT: This article makes a case for a reconceptualisation of aid and development programme design. Specifically, it questions the role of the international "development expert" in the design and implementation process. We argue that by employing "design thinking" as a guiding principle, the way in which aid programmes are envisaged and delivered can be radically overhauled, resulting in dramatically improved outcomes for the users of aid. We argue that practical improvements in delivery are achievable through locally rooted, "user-driven" development solutions that originate from the beneficiaries themselves. Design thinking as applied here goes significantly further than other programme design and implementation methodologies that champion locally owned, needs-driven assistance. Furthermore, we make a case for this approach addressing wider problems within the sector, namely the perception, in some quarters, that aid is intrinsically "neo-imperialist" in design and ideologically driven.